"They Just Say Organic Food Is Healthier": Perceptions of Healthy Food among Supermarket Shoppers in Southwest Baltimore. (December 2014) - Rodman, Sarah O.; Palmer, Anne M.; Zachary, Drew A.; Hopkins, Laura C.; Surkan, Pamela J.
Abstract To discover how organic food factors into low‐income consumers' overall understanding of healthy eating, we analyzed 36 in‐depth interviews with adults in Baltimore, Maryland. We asked participants to discuss their understanding of healthy eating. Unprompted, many participants discussed organic food or attributes commonly understood to define organic food. Some participants believed health issues including cancer, weight gain, and allergies can arise from consuming nonorganic foods. Participants expressed that organic competes with other food attributes such as nutrient content in informing their perception of whether a food is healthy. Several voiced concern that nonorganic foods are responsible for weight gain and abnormal development. Our results show that despite limited access, organic is an important factor in some consumers' understanding of healthy food. Consumers' perceptions of organic can swamp or compete with other messages about healthy eating. Therefore, consumers' understanding of organic should be considered in developing diet‐related messages and programs.